Toni Morrison's spiritual vision : faith, folktales, and feminism in her life and literature - Nittle, Nadra (Minneapolis, Minnesota : Fortress Press, 2021)
Toni Morrison's Spiritual Vision unpacks an oft-ignored but essential element of her work--her religion--and in so doing gives readers a deeper, richer understanding of her life and her writing. As Nadra Nittle's wide-ranging, deep exploration of Morrison's oeuvre reveals, to fully understand Morrison's work, one must also understand the role of religion and spirituality in her life and literature.
Black, Christian, and feminist : Toni Morrison's village literature -- A magical Black heritage -- Black and Catholic : a long tradition -- Sula's deconstruction of the Madonna, the whore, and the witch -- The folklore and holy women of Song of Solomon and Beloved -- Paradise's Black Madonna and Afro-Catholicism -- A literary legacy of resilience.
Includes bibliographical references (pages 177-184) and index.
Online resource; title from digital title page (viewed on July 28, 2021).
JSTOR
Keywords: Morrison, Toni -- Criticism and interpretation; Morrison, Toni; Religion in literature; Religion dans la littérature.; Religion in literature; Criticism, interpretation, etc